Intellectual Capital dan Nilai Perusahaan: Studi pada IDX ESG Leaders - Fauziah, Farah Nur (CV. ITTC INDONESIA, 2025)
The Indonesian economy is currently grappling with substantial challenges in the aftermath of the global pandemic, characterized by a pronounced economic slowdown and mounting international pressure. Intellectual capital, comprising employed capital, innovation capital, relational capital, human capital, and structural capital, constitutes one of the strategies that contributes to economic resilience and corporate sustainability. The objective of this study is to analyze the influence of employed capital, innovation capital, relational capital, human capital, and structural capital on company value. The present study employed a quantitative method. The data utilized in this study were secondary data, collected from annual reports of companies listed on the IDX ESG Leaders, with a total of 110 observations. The data analysis employed was multiple linear regression. The findings of the study suggest that employed capital, innovation capital, and relational capital exert a significant influence on company value. Conversely, human capital and structural capital have been demonstrated to exert no influence on company value.